1994
DOI: 10.1002/art.1780371118
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome‐restricted antibodies are detected before anti‐dsdna and/or antihistone antibodies in serum of mrl‐mp lpr/lpr and +/+ mice, and are present in kidney eluates of lupus mice with proteinuria

Abstract: Objective. To compare the humoral response to nucleosomes with the response to their individual components (double-stranded DNA [dsDNA] and histones) and to assess the involvement of antinucleosome antibadies in immune deposits in the kidney of MRL mice.Methods. We used enzyme-liked immunosorbent assays of sera and kidney eluates for antibody activity against purified nucleosomes, dsDNA, and histones.Results. Antinucleosome antibodies emerged before anti-dsDNA and antihistone antibodies. A fraction of antinucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
138
0
5

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 194 publications
(150 citation statements)
references
References 13 publications
6
138
0
5
Order By: Relevance
“…Nucleosomes from apoptotic cells are shown to be immunogenic for pathogenic autoantibody-inducing T cells in lupus (7). Antinucleosome antibodies are found to be present before anti-double-stranded DNA and antihistone antibodies in MRL-lpr mice (8). Analysis of the relationship between PCD and autoantibody production would contribute to the elucidation of the mechanisms of autoantibody production in SS.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleosomes from apoptotic cells are shown to be immunogenic for pathogenic autoantibody-inducing T cells in lupus (7). Antinucleosome antibodies are found to be present before anti-double-stranded DNA and antihistone antibodies in MRL-lpr mice (8). Analysis of the relationship between PCD and autoantibody production would contribute to the elucidation of the mechanisms of autoantibody production in SS.…”
Section: Discussionmentioning
confidence: 99%
“…Age-matched animals of the same sex (female) were used in each experiment. In the present study, MRLϩ/ϩ mice were classified into three groups, according to their serum autoantibody pattern (as assessed by enzyme-linked immunosorbent assay) during the course of disease; 10-week-old pre-autoimmune mice (antichromatin antibody negative), 20-to 30-week-old (anti-nucleosome antibody positive), and 30-to 40-week-old mice (anti-nucleosome and anti-dsDNA antibody positive) [3].…”
Section: Micementioning
confidence: 99%
“…The in vivo basic unit of chromatin, the nucleosome (composed of a histone octamer wrapped by ϳ160-180 of helical base pairs DNA) appears to play a crucial role in the induction of disease. The detection in murine lupus of nucleosome-specific antibodies before the appearance of antibodies directed against its individual components, dsDNA and histones [2,3], and the presence of nucleosome-specific pathogenic T cells in the periphery of young, pre-autoimmune (NZB ϫ SWR)F1 lupusprone mice [4] indicates early autoimmunization with nucleosomes in murine lupus. Similar observations have been made in lupus patients as nucleosome-specific antibodies are detected with high occurrence (80-90%) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nucleosome-restricted antibodies in sera of patients with SLE was reported previously ( 1 9). In addition, nucleosomes have recently been found to be a major immunogenfor induction of autoantibodies in T cells of lupus-prone mice (8), and antibodies to nucleosomes were detected in plasma of such mice prior to the appearance of anti-dsDNA and anti-histone antibodies (9). These results suggest that antibodies to nucleosomes are specifically related to the pathogenesis of SLE.…”
Section: Discussionmentioning
confidence: 87%
“…Nucleosomes, the unit of DNA-histone complexes, rather than naked DNAor free histones have been detected in plasma ofSLE patients (7). In addition, nucleosomes have recently been found to be a major immunogenfor autoantibody-inducing T cells (8) , and antibodies to nucleosomes have been detected earlier than anti-double-stranded (antidsDNA) and anti-histone antibodies in lupus-prone mice (9). The LE factor is an antibody to DNA-histone complexes, but not to free histones or DNAitself (10, ll demonstrated that the binding between antigens and antibodies is dependent upon the presence of anions with an electrostatic influence (12).…”
Section: Introductionmentioning
confidence: 99%